Identification of Effective Factors in Recurrence of Schizophrenia Spectrum Disorder Using Poisson Regression Model - Omran Davarinejad; Tahereh Mohammadi Majd; Masoumeh Abbasi; Soudabeh Eskandari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2021)
Background and Objectives: Schizophrenia is one of the most severe psychiatric disorders that has a recurrent nature. Frequent relapses have destructive impacts on patient’s thoughts, behaviors and relationships. These can lead to disruption of personal and social performance of patient. The aim of this study was to identify risk factors for increasing the number of relapses. Methods: In this retrospective cohort study, data from medical records of individuals with SSD who were admitted at least once to Farabi Hospital between 2015 and 2019 years extracted. To determine factors related to recurrence of Schizophrenia, Univariate and multivariate analysis and multivariate Poisson Regression were performed respectively. Analysis was done using STATA 14.1. Results: Based on extracted data from 401 medical records, 255 (63.6%) were males and 146 (36.4%) were females. A total of 1105 relapse were observed in males with 683 cases, and females with 422 cases. 65 patient experienced relapse from 5 to 11 times. Among considered variables, Employment status (RR=0.85, P-value=0.043), age (RR=0.99, P-value=0.03), Mode of Onset (RR=0.78, P-value=0.027) and Medication Adherence (RR=1.67, P<0.001) were significant on increasing readmission. Conclusion: According to the results of this study, the young age of onset of schizophrenia, the gradual onset of the disorder, unemployment and drug non-compliance had a significant effect on increasing the risk of recurrence in patients with schizophrenia. considering above risk factors, it seems necessary to perform preventive and therapeutic measures to reduce the risk of relapses. Patients with non-adherence can be under education and counseling.